Analisis Dasar Perencanaan Pelabuhan di Rencana Ibu Kota Negara (IKN) Baru - Provinsi Kalimantan Timur - Irwan, Asep; Fatkhurrozi, Muhammad (Universitas Batanghari Jambi, 2024)
In the transportation system, the port is a node in the chain of smooth sea and land transportation cargo, which then functions as a transition activity between modes of transportation. The importance of ports in a transportation system requires that each port have a basic framework for port development and construction plans. This basic framework is contained in a spatial development plan which is then described in stages of short, medium andl ong term development implementation. Port development studies are an integral activity in transportation planning in the development of the National Capital City (IKN). This research begins with an analysis of goods movement needs and location analysis. These two factors are the main factors determining port layout. Location analysis includes available land conditions, topographic conditions, hydrooceanographic conditions, including the available road network. It is known that the need for construction goods supplied from outside Kalimantan is 54,037,806 tons for 5 years. Thus, the annual average is 10.8 million tons. Assuming there are 260 working days in a year, then there is a flow of 41,569.2 tons per day. The existing port or terminal that will be developed into an IKN port is the PT Special Terminal. ITCI Hutani Manunggal (IHM) with planned activities for loading and unloading construction goods and the East Kalimantan Kariangau Port Terminal (KKT) loading and unloading civil logistics goods.